The governance of integrated regional development and the role of geographical information systems: Managing complex information relations between two different worlds - Arjan Venrooy (European Regional Science Association (ERSA), 2005)
One the one hand the creation of a standardized and open geo-graphical infrastructure could facilitate the process of regional development, because the incentive for dysfunctional information politicking, in relation to the protection of specific interests and frames of reference, has to some extent disappeared. One the other hand there is possible tension between the need for tailor-made, regional focused planning solutions and the standardized nature of these nation wide infrastructures. What does the emergence of the standardized nation wide geographical information infrastructures, and the supply of information which can be generated by this infrastructure, imply for the process of co-production in local and regional, and thus contingent, urban and rural planning practices and the information and knowledge needs which are expressed in the local practices by relevant stakeholders? What does this imply for the management of information relations in these local planning and regional development practices. This is a relevant question because both the world of geographical system development and the world of integrated regional planning are separated worlds, with their own 'rules' and dynamic. In order to address this question we will look at a specific case of integrated regional planning and to look which factors facilitate or frustrate the effective and efficient coordination between the supply of information by these nation wide geographical infrastructures and the information needs of the actors, which are involved in a shared regional development process. This will be the Blue City initiative ('Blauwe Stad') in Groningen.
Keywords: 330